2017
DOI: 10.5194/acp-17-8101-2017
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Arctic aerosol number size distributions: seasonality and transport patterns

Abstract: Abstract. The Arctic environment has an amplified response to global climatic change. It is sensitive to human activities that mostly take place elsewhere. For this study, a multi-year set of observed aerosol number size distributions in the diameter range of 10 to 500 nm from five sites around the Arctic Ocean (Alert, Villum Research Station -Station Nord, Zeppelin, Tiksi and Barrow) was assembled and analysed.A cluster analysis of the aerosol number size distributions revealed four distinct distributions. To… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
158
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(192 citation statements)
references
References 79 publications
30
158
4
Order By: Relevance
“…The lower g values at the five Arctic sites during the summer indicate the presence of smaller particles, probably due in part to wet scavenging of larger particles and/or new particle formation. Both processes tend to be more common in the summer (e.g., Freud et al, 2017) and are consistent with the lower scattering coefficients observed in the summer. Higher g values throughout the rest of the year represent larger particles, Figure 7.…”
Section: Spatiotemporal Variability Of Aerosol Optical Properties In supporting
confidence: 81%
“…The lower g values at the five Arctic sites during the summer indicate the presence of smaller particles, probably due in part to wet scavenging of larger particles and/or new particle formation. Both processes tend to be more common in the summer (e.g., Freud et al, 2017) and are consistent with the lower scattering coefficients observed in the summer. Higher g values throughout the rest of the year represent larger particles, Figure 7.…”
Section: Spatiotemporal Variability Of Aerosol Optical Properties In supporting
confidence: 81%
“…formation. Both processes tend to be more common in the summer (e.g., Freud et al, 2017) and are consistent with the lower scattering coefficients observed in the summer. Higher g values throughout the rest of the year represent 10 larger particles, perhaps due to long range transport.…”
supporting
confidence: 81%
“…The OM peak is coincident with the maximum in MSA and decreasing ss-Na + , suggesting that the May peak in OM may be partly influenced by secondary processes associated with marine sources. The maximum in OM / nss-SO = 4 occurs in August, which is also when new particle formation at Alert is a maximum (Leaitch et al, 2013;Freud et al, 2017). The O / C August peak is entirely due to the summer of 2013: August O / C is 0.47 in 2012, 1.67 in 2013 and0.53 in 2014 (also, see Sect.…”
Section: Functional Groups and Oxygenationmentioning
confidence: 86%